Immunoglobulin therapy in the 21st century: the dark side of the moon - Albert Farrugia (Frontiers Research Topics, 2015)
In the early decades since the introduction in the early '80s of immunoglobulin therapy many studies tried to identify which clinical indications might benefit from the therapy, which treatment's schedules are effective and safe. It is universally accepted that immunoglobulin therapy is a life-saving treatment in patients with PID. The rise of new indications for further different clinical conditions resulted in a steady increase in demand for immunoglobulins. Currently the consumption of immunoglobulin for PID represents a small fraction of the market. In the recent past we have been observing: 1) An increase in the demand for plasma and in the consequent need to increase the number of donors; 2) Changes in methods to improve IgG recovery and to increase productivity as a response to growing clinical demand; 3) Introduction of immunoglobulin treatments with higher concentration; 4) Changes in the timing of administration with an increase in the rate of infusion; 5) Introduction of immunoglobulin treatment administered subcutaneously mainly confined initially to patients with PID and later extended to other clinical indications which often require higher volumes of infusion. Doctors following patients with PID were initially alarmed only to a possible risk of shortage. More relevant and less discussed appear the possible consequences of: 1) the risk of an improper transfer of information on treatments from a clinical indication to another. In particular, the idea of a mere replacement function in patients with PID might possibly be borrowed from the model of other clinical conditions requiring a replacement such as haemophilia. In PID, immunoglobulin treatment instead is obviously replacing a missing feature. However, other immune alterations are responsible for the large number of PID-associated diseases including inflammatory manifestations and tumors, common causes of morbidity and mortality. The immunomodulatory effects of immunoglobulin administered at replacement dosages on multiple cells and immune system functions are still largely to be checked in in vitro studies and in vivo. 2) the changes in the immunoglobulin production and schedules of administration. These should have been assessed in studies of drug surveillance, necessary in order to evaluate on large numbers of what it is initially reported on patients enrolled in the pivotal clinical trials, usually in the absence of most of the main disease-associated clinical conditions affecting pharmacokinetics, efficacy and tolerability. Severe side effects are now more frequently reported. This requires surveillance studies in order to verify the tolerability. Nowadays, personalized health research presents methodologic challenges, since emphasis is placed on the individual response rather than on the population. Even within a universally accepted indication, such as in PID, the identification of prognostic markers should guide the therapeutic intervention. 3) the risk of a decrease in the surveillance and monitoring of PID-associated clinical conditions. In fact, self- administration of immunoglobulins administered subcutaneously increased the independence of a number of patients. On the other hand, it led to the reduction in the number of contacts between specialized centers and patients who often require a close monitoring of disease-associated conditions. A wide debate between experts is necessary to afford the new challenge on immunoglobulin usage.